Digging the Neolithic stamp-seals of SE Europe from archaeological deposits, texts and mental constructs - Prijatelj, Agni (Documenta Praehistorica, 2007)
The article presents the archaeological and experimental data on the Neolithic stamp- seals from phenomenological perspective. An alternative view to their production, consumption and symbolic values is proposed by employing concepts of affordances, constraints, icons, indexes and symbols. It is argued that the stamp-seal motifs probably conveyed specific information, while objects were included in various networks of meaning. Similar importance is given to the fact that the stamp-seals probably evolved a secondary mode of use.
Keywords: severovzhodna Evropa; arheološke najdbe; neolitik; pečatniki; žigi; motivi; simboli; symbol